Time trends for the use of active surveillance and deferred treatment for localised prostate cancer in Sweden: a nationwide study - Jovana Maljkovic; Anna Bill-Axelson; Hampus Hållberg; Anders Berglund; Pär Stattin; Ola Bratt (Scandinavian Journal of Urology)
Objective: Active surveillance (AS) is recommended for low-risk and some favourable intermediate-risk prostate cancers, but criteria for AS and deferred treatment have changed over time. We assessed time trends for the use of AS and deferred treatment.